Polyketides with a 6/6/6/6 Oxaphenalene Pyranone Skeleton from Marine-Derived Streptomyces sp. HDN150000 - Xiaoting Zhang; Falei Zhang; Wenxue Wang; Xingtao Ren; Tianjiao Zhu; Qian Che; Dehai Li; Guojian Zhang (Marine Drugs)
Three new structures named naphpyrone I–K (1–3) that contain a 6/6/6/6 oxaphenalene pyranone skeleton were isolated and purified from a marine-derived Streptomyces sp. HDN155000. Their chemical structures, including configurations, were elucidated by extensive NMR, MS, single-crystal X-ray diffraction, theoretical NMR calculations, DP4+ probability analysis, and ECD analyses. Naphpyrone K (3) showed cytotoxic activities against L-02, K562, NCI-H446/EP, MDA-MB-231, and NCI-H446 cancer cells with IC50 values of 5.13, 3.34, 2.50, 2.61, and 2.20 μM, respectively. These findings highlight the potential for screening and developing therapeutic drugs from aromatic polyketides derived from marine actinobacteria.